Effects of Foliar Fertilization on Nutrient Uptake, Yield, and Fruit Quality of Pomelo (Citrus grandis Osbeck) Grown in the Mekong Delta Soils - Le Van Dang; Ngo Phuong Ngoc; Ngo Ngoc Hung (International Journal of Agronomy)
Foliar application is a popular technique to supply mineral nutrients to crops. It also enhances nutrient use efficiencies, especially under limited soil fertility or restricted environmental conditions. This study aimed to evaluate the influence of foliar application of phosphorus (P) with potassium (K), magnesium (Mg), and zinc (Zn) on the nutrient uptake, yield, and fruit quality of pomelo. The experiments were conducted between 2018 and 2021 in three different sites of alluvial soils, including four treatments, namely, control (without foliar fertilization), FF1 (containing P, K, and Mg), FF2 (P, K, Mg, and Zn), and FF3 (Zn). The results indicated that the P, K, and Mg concentrations in leaves and fruits were significantly enhanced after the spraying of solutions FF1 and FF2 compared with the control and FF3. The application of FF1 and FF2 greatly improved the fruit quality, and the fruit yield response was as high as 4.0-5.0 t ha−1. Foliar Zn application (FF3) increased the Zn concentration in leaves, but there was no improvement in fruit Zn content, fruit quality, and yield compared to the control treatment. The results indicate that FF1 or FF2 could be used as a sustainable fertilizer strategy for pomelo trees because of its ability to improve the leaf and fruit nutrient concentration and enhance the fruit quality and productivity of pomelo.